Determinants Of The Incident Of Hypertension In The Working Area Of The New City Puskesmas, Melawi District, 2023 - Damayanti, Ria; Dwi Saroso Libra Putra; Sohibun, Sohibun; Rika Yuanita Pratama; Sunarti, Sunarti (Sean Institute, 2023)
Hypertension occurs when systolic and diastolic blood pressure is too high. Hypertension is a condition when measured on two different days, the systolic blood pressure reading on both days is ≥140 mmHg and/or the diastolic blood pressure reading on both days is ≥90 mmHg (WHO, 2019). Objective: To determine the determinants of hypertension in the work area of the Kota Baru Health Center, Melawi Regency. Method: This research was carried out using quantitative methods with a cross sectional design, a population of 15,872, and using the Stanley Lemeshow formula, 100 samples were obtained using the Portional Random Sampling sampling technique. The instrument used was a closed questionnaire by means of an interview. Data analysis was carried out using the Chi-Square test. Results: There is a relationship between Knowledge (p-value = 0.008, OR = 3.378 95%), Attitude (p-value = 0.016, OR = 3.114), Smoking Habits (p-value = 0.012, OR = 3.194) and Diet (p -value = 0.036, OR = 2.768) with the incidence of hypertension in the working area of the Kota Baru Health Center, Melawi Regency. Conclusion: There is a relationship between knowledge, attitudes, smoking habits and patterns with the incidence of hypertension in the work area of the Kota Baru Health Center, Melawi Regency. Suggestion: The community health center health promotion program can be more active in providing education to the people of Tanah Pinoh sub-district, especially to people with hypertension. Providing information regarding the need for counseling on the prevention of hypertension and programs related to health education in the adult population so that it can prevent an increase in the prevalence rate of hypertension.